PENGARUH SUPERVISI AKADEMIK DAN IKLIM ORGANISASI TERHADAP PROFESIONALISME GURU SEKOLAH DASAR DI KECAMATAN BUMIAYU - Arinda Festi Pratiwi; Noor Miyono; Titik Haryati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The problems in this research are (1) is there an influence of academic supervision on the professionalism of elementary school teachers in Bumiayu District? (2) What is the influence of organizational climate on the professionalism of elementary school teachers in Bumiayu District? (3) Is there an influence of academic supervision and organizational climate on the professionalism of elementary school teachers in Bumiayu District? The aims of this research are (1) to determine the magnitude of the influence of academic supervision on the professionalism of elementary school teachers in Bumiayu District, (2) to determine the magnitude of the influence of organizational climate on the professionalism of elementary school teachers in Bumiayu District, (3) to determine the magnitude of the influence of academic supervision and climate organizations together on the professionalism of elementary school teachers in Bumiayu District. The population in this study were all elementary school teachers in Bumiayu District, Brebes Regency, totaling 581 people. A sample of 237 people was obtained using a simple random sampling technique. The data collection method used is the questionnaire method. The data analysis used is descriptive analysis, requirements testing and hypothesis testing which includes simple linear regression analysis to determine: (1) the influence of academic supervision on teacher professionalism, (1) the influence of organizational climate on teacher professionalism, and multiple regression analysis to determine the influence of supervision academic and organizational climate together on teacher professionalism. To find out the data, use the SPSS For Window Release 23 program facilities. From the research results, it can be seen that the average academic supervision score is 115.5, including the good category, the average organizational climate score is 183.56 in the good category, and the average teacher professionalism score is 130.0 in the good category. professional. The prerequisite test results from the research data showed that the data was normally distributed, homogeneous, linear, not multicollinear and there was no heteroscedasticity. From the hypothesis test it was found: (1) there is a positive influence between academic supervision on teacher professionalism of 42%, (2) there is a positive influence between organizational climate on teacher professionalism of 46.9%, (3) there is a joint influence between supervision academic and organizational climate on teacher professionalism was 49.2%.